Silencing and freedom of speech in UK higher education. (5th August 2020) - Malcolm, Finlay
Abstract : Freedom of speech in universities is currently an issue of widespread concern and debate. Recent empirical findings in the UK shed some light on whether speech is unduly restricted in the university, but it suffers from two limitations. First, the results appear contradictory. Some studies show that the issue of free speech is overblown by media reportage, whilst others track serious concerns about free speech arising from certain university policies. Second, the findings exclude important issues concerning restrictions to speech on campus that fall outside the traditional debate around violations to free speech rights. This is particularly the case when certain voices are excluded from important policy conversations, and in issues around diversifying the curriculum. This article overcomes these two limitations by developing a novel conceptual framework within which to situate current debates concerning speech‐related matters in universities. It does so by developing a taxonomy around the concept of 'silencing'. It then considers the current issue of speech matters in universities within this framework to determine whether, and to what extent, speech is indeed unduly restricted, and where this is a concern for free speech violations, and where it falls outside this issue.